Vitamin D status in critically ill children admitted to pediatric intensive care unit with relation to outcome - R Satapathy Jyoti; K Meher Bijay; D Pradhan Deepti; Mahar Jatadhari; K Maji Benoj; K Routray Rakesh (Wolters Kluwer Medknow Publications, 2018)
Background: Vitamin D deficiency (VDD) is highly prevalent in critically ill children. Although its role in immunity is hypothesized, its role in mortality is not clear. Objectives: To study the prevalence of VDD in critically ill children and its effect on outcome. Material and Methods: This prospective observational study was done at a tertiary care PICU from Nov 2016 to Dec 2017. Critically ill children (aged 1 month to 14 years) were enrolled for study. 25(OH) Vitamin D estimation was done within 24 hour of admission. Outcome measures recorded were PRISM III score, need of mechanical ventilation, ICU stay duration and death. Descriptive analysis, independent sample 't' test, Mann-Whitney U test done with SPSS 24 and ROC analysis done. Results: Out of 78 children, 52 (66.7%) were VDD. There was no significant difference in PRISM III score, predicted mortality at admission and need of mechanical ventilation between children with and without VDD. VDD group had younger age at admission (54.85±53.12 vs. 78.54±64.55mo, p 0.048) and longer PICU stays (10.15±12.30 vs. 4.23±2.69 days, p 0.018). Mortality was insignificantly higher in VDD group (p=0.477). In prediction of mortality, vitamin D is a poor predictor of outcome (AUC 0.557, p 0.479) with low sensitivity (45.45%) and specificity (85.71%) as compared to PRISM III score (AUC 0.747, p= 0.0001). Conclusions: High prevalence of VDD is seen in critically ill children. Children with VDD have younger age at admission, longer ICU stay without significantly higher mortality. VDD is a poor predictor of mortality in critically ill children.